The Moral Imperative of Human Capital: A Philosophical Analysis of HR Development for Sustainable Economic Growth in Indonesia - Adi Sucipto; Heri Pratikto; Agung Winarno (Enigma Institute, 2025)
This study examines the philosophical underpinnings of human resource development (HRD) in Indonesia, arguing that a morally grounded approach to HRD is crucial for sustainable economic growth. It explores the interconnectedness of ethical considerations, human capital development, and sustainable economic progress within the Indonesian context. This research employs a qualitative approach, utilizing a critical analysis of relevant literature on economic philosophy, human development, and sustainable development. It draws upon the works of influential thinkers like Amartya Sen, Martha Nussbaum, and Alasdair MacIntyre to establish a conceptual framework. Additionally, it analyzes policy documents and reports related to HRD and sustainable development in Indonesia. The study reveals a significant gap between the rhetoric of human capital development and the actual implementation of HRD practices in Indonesia. It identifies a tendency to prioritize technical skills development over ethical and moral formation, which hinders the cultivation of a workforce capable of contributing to sustainable economic growth. In conclusion, this research advocates for a paradigm shift in Indonesia's HRD approach, emphasizing the integration of moral philosophy into HRD policies and practices. It proposes a framework that prioritizes the development of virtues such as integrity, social responsibility, and environmental consciousness, alongside technical skills, to foster a workforce committed to sustainable economic development.